Cronaca dal convegno: ‘Verso un codice di condotta per i parlamentari. Le esperienze internazionali a confronto’ - Del Vecchio, Ilaria; Di Majo, Luca (Cultura giuridica e diritto vivente, 2015)
[Chronicle from conference: ‘Towards a code of conduct for members of Parliament. An overview on international experience’. Parliamentary seminar, Camera dei deputati, 4th of June 2015] This paper summarizes reports presented during the international meeting on parliamentary code of conduct, held at the Italian Parliament on the 4th of June 2015.